If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -10 = 50 + -2x Reorder the terms: -10 + 3x = 50 + -2x Solving -10 + 3x = 50 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. -10 + 3x + 2x = 50 + -2x + 2x Combine like terms: 3x + 2x = 5x -10 + 5x = 50 + -2x + 2x Combine like terms: -2x + 2x = 0 -10 + 5x = 50 + 0 -10 + 5x = 50 Add '10' to each side of the equation. -10 + 10 + 5x = 50 + 10 Combine like terms: -10 + 10 = 0 0 + 5x = 50 + 10 5x = 50 + 10 Combine like terms: 50 + 10 = 60 5x = 60 Divide each side by '5'. x = 12 Simplifying x = 12
| x^2+12*x-7=5*x+1 | | 7+2x=3x-4 | | -10x-23=-8x+17 | | 2x+(-11x)+44+3=77 | | 5-11g=7(5-2g) | | x^2-7*x+6=0 | | 6(-3x+2)=120 | | 64x^2-9x^2=0 | | x^2+7*x+14=4 | | 5x^2-23x-42= | | 6x+2(3+x)=7x+1 | | 4n+7=n | | -4x+32=5x-4 | | x^2+8*x-20=0 | | 5-3(2x+1)=4(x+5)+6 | | 6(x+3)+1=33 | | -15-12x=13-10x | | 8b^5/64b^4 | | 6x+120=360 | | 9x-13=2x+8 | | -14=5+t | | 8(a-5)+5a=-118 | | [2x+1]=10 | | 4(x-5/2)^2=15/2 | | 4x-5+2x=35+8x | | 2+10x=9x-16-7 | | 11x-2x=17 | | 29x-56=x-53 | | 8-6m=5-18m+3 | | -2.1x+0.4+0.8x+2x+0.6= | | 21+2n=4n-63+5n | | 4.6x-1.2=-28.8 |